Managing Software Requirements the Agile Way Bridge the Gap Between Software Requirements and Executable Specifications to Deliver Successful Projects - Heath, Fred (Packt Publishing, Limited, 2020)
Studies on software project delivery show that the most common cause of failure is mismanagement of the project's requirements. This book takes a holistic approach to managing requirements to show you how to bridge the gap between requirements and specifications and deliver a successful software project that meets your client's expectations.
Description based upon print version of record
Keywords: Computer software -- Development -- Management; Computer software; Development; Management